Green-High-Performance PMMA–Silica–Li Barrier Coatings - Trentin, Andressa [UNESP] (2022)
Organic-inorganic coatings based on polymethyl methacrylate (PMMA)–silica–lithium are an efficient alternative to protect metals against corrosion. Although the preparation methodology is established and the thin coatings (~10 µm) are highly protective, the use of an environmentally friendly solvent has not yet been addressed. In this work, PMMA–silica coatings were synthesized using 2-propanol as a solvent and deposited on aluminum alloy AA7075, widely used in the aeronautical industry. Different concentrations of lithium carbonate (0–4000 ppm) were incorporated into the hybrid matrix to study the structural and inhibitive effects of Li+ in terms of barrier efficiency of the coatings in contact with saline solution (3.5% NaCl). Structural and morphological characterization by low-angle X-ray scattering, X-ray photoelectron spectroscopy, atomic force microscopy, thermogravimetric analysis, thickness, and adhesion measurements, showed for intermediate lithium content (500–2000 ppm) the formation of a highly polymerized PMMA phase covalently cross-linked by silica nodes, which provide strong adhesion to the aluminum substrate (15 MPa). Electrochemical impedance spectroscopy (EIS) results revealed an excellent barrier property in the GΩ cm2 range and durability of more than two years in a 3.5% NaCl solution. This performance can be attributed to the formation of a highly reticulated phase in the presence of Li, which hinders the permeation of water and ions. Additionally, the self-healing ability of scratched samples was evidenced by EIS assays showing a fast Li-induced formation of insoluble products in damaged areas; thus, constituting an excellent eco-friendly solution for corrosion protection of aerospace components.